2016
DOI: 10.1007/s00586-016-4534-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for proximal junctional kyphosis: a meta-analysis

Abstract: The results of our meta-analysis suggest that age at surgery >55 years, fusion to S1, T5-T12 >40°, low BMD and SVA difference >5 cm are risk factors for PJK. However, gender, combined anterior-posterior surgery, use of pedicle screw at top of construct, hybrid instrumentation and thoracoplasty are not associated with PJK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 39 publications
2
85
1
1
Order By: Relevance
“…18,19 The incidence ranges between 10-40%, with reported risk factors including advanced age at surgery, fusion to sacrum, thoracic kyphosis >40˚, low T-score, larger amount of correction, and sagittal vertical axis (SVA) difference >5 cm. 20 However, our findings indicated that proximal and distal junctional kyphosis occurred more frequently in the CoCr group than in the Ti group. The Young's modulus of cortical or cancellous bone ranges from 10.4 GPa-20.7 GPa-much lower than that of Ti or CoCr-and the elastic modulus of CoCr is superior to that of Ti.…”
Section: ‫ܫ‬ = ߨ݀ ସ 64mentioning
confidence: 51%
“…18,19 The incidence ranges between 10-40%, with reported risk factors including advanced age at surgery, fusion to sacrum, thoracic kyphosis >40˚, low T-score, larger amount of correction, and sagittal vertical axis (SVA) difference >5 cm. 20 However, our findings indicated that proximal and distal junctional kyphosis occurred more frequently in the CoCr group than in the Ti group. The Young's modulus of cortical or cancellous bone ranges from 10.4 GPa-20.7 GPa-much lower than that of Ti or CoCr-and the elastic modulus of CoCr is superior to that of Ti.…”
Section: ‫ܫ‬ = ߨ݀ ସ 64mentioning
confidence: 51%
“…To allocate a maximum of 9 points for the quality of selection, exposure, comparability, and results for study participants, this scale for nonrandomized case-controlled studies and cohort studies was applied. [29] …”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was analyzed with I 2 test, in which I 2  > 50% implies heterogeneity. [29] All statistical analyses were conducted by using RevMan 5.3 (The Cochrane Collaboration, Oxford, UK) and STATA 12.0 (Stata Corporation, College Station, TX). Sensitivity analysis was conducted to examine the influence of excluding each study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the development of PJK has been suggested to be associated with patient demographics. 6,10,11 These risk factors were recently identified and studied in a systematic literature review and meta-analysis. The results reported are extensive and demonstrate the relationship between more than 20 risk factors and PJK development.…”
Section: Introductionmentioning
confidence: 99%